Permutations from APN power functions over F 2 2n - Shi-zhu TIAN (网络与信息安全学报)
APN functions have the lowest differential uniform over finite fields with characteristic 2 and the APN power functions are the most classical ones.APN power functions are all 3-1 functions over F 2 2n .By generalizing the idea of changing 2-1 functions to 1-1 functions over finite fields with odd characteristics,methods to change 3-1 functions over finite fields with even characteristics into permutations were obtained and permutations from APN power functions over F 2 2n were constructed.According to the construction,the differential properties of permutations obtained by this method were discussed.